Early hydration and hardening of OPC-CSA blends for cementitious structure of 3D printing. (2nd October 2020) - Kim, Seonghoon; Kim, Taewoo; Kim, Buyoung; Kim, Hong-dae; Kim, Jaeyoung; Lee, Heesoo
ABSTRACT: The buildability of cementitious structure for 3D printing was investigated in terms of ettringite formation and hardening behaviour with packing density of OPC-CSA blends. The packing density of the OPC was 2.34 g cm −3, increased to 2.39 g cm −3 when 10 wt-% CSA was added, and then began to decrease to 2.37 g cm −3 at 15 wt-% CSA addition. The exothermic peak was observed at around 114°C which is the formation temperature of ettringite, and the exothermic value of ettringite was 2.42 mW mg −1 (OPC), increased to 3.27 mW mg −1 (CSA 10 wt-%), and then started to decrease from 2.72 mW mg −1 (CSA 15 wt-%). For the quantitative analysis of ettringite formation, the amount of ettringite formation in OPC was 5.87%, but increased rapidly with the addition of CSA, showing the maximum value 9.49% at 10 wt-% CSA addition. The formation of needle-shaped ettringite was observed in all OPC-CSA blends, and the intertwined structures were appeared as the amount of ettringite formation increased. The flexural strength of OPC was 0.88 MPa, but increased rapidly according to the addition of CSA, and the maximum strength was 2.88 MPa at 10 wt-% CSA with the largest amount of ettringite formation.